Nurse to Nurse Dementia Care: Expert Intervenions - Steele, Cynthia D. (McGraw-Hill, 2020)
The new Nurse to Nurse series is specifically designed to simulate the teaching experience nurses learn best from: trusted mentors carefully explaining what they must do in specific clinical situtions. Written in a consistent, single-author voice, this series brings the wisdom and experience of some of the foremost experts to non-specialist nurses in clinical care...